Delayed Versus Immediate Pushing in the Second Stage of Labor in Women With Neuraxial Analgesia: A Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 2 (June 2021) - Di Mascio, D.; Saccone, G.; Bellussi, F.; Al-Kouatly, H.B.; Brunelli, R.; Panici, P.B.; Liberati, M.; D'Antonio, F.; Berghella, V.
Abstract : ( Am J Obstet Gynecol . 2020;223:189–203) Maternal and perinatal outcomes are influenced by several variables in second-stage labor management, including neuraxial analgesia, oxytocin use, parity, fetal position, maternal characteristics, and neonatal birthweight. Thus, many strategies have been evaluated which assess proper management strategies for second-stage labor. Once a woman achieves complete cervical dilation, she can begin pushing immediately or she can delay pushing. The aim of this meta-analysis and systematic review was to evaluate the effects of immediate compared to delayed pushing during the second stage of labor on mode of delivery for women with neuraxial analgesia.